(untitled) (Comprehensive Journal of Science, 2026)
While the normal course of action is for a dispute to continue until a judgment is issued , something may occur that alters this course . This is called a procedural defect . The term procedural defects refers to those factors that weaken a case from a formal standpoint , leading to its stagnation or termination without a ruling on its merits . These defects are specifically defined in the Libyan Code of civil procedure .